2007
DOI: 10.1007/s12098-007-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral palatal palsy with viral hepatitis

Abstract: Isolated unilateral palatal (velopalatopharyngeal) palsy is a clinical rarity. This usually presents in a child as acute onset rhinolalia, unilateral absent palatal reflex and pharyngeal asymmetry with a benign self-resolving course. Etiology remains controversial. We report association of this entity in a male child with viral hepatitis A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…3 However, definitive evidence in the form of positive viral serology / culture could be demonstrated in only five of the twelve cases with a febrile prodrome. 3,5 The second hypothesis has been proposed by Lapresle et al 6 They demonstrated the existence of ischemia in the roots of the glossopharyngeal and vagus nerves. The cause of this ischemia is not known and viral infection induced vasculitis cannot be ruled out.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…3 However, definitive evidence in the form of positive viral serology / culture could be demonstrated in only five of the twelve cases with a febrile prodrome. 3,5 The second hypothesis has been proposed by Lapresle et al 6 They demonstrated the existence of ischemia in the roots of the glossopharyngeal and vagus nerves. The cause of this ischemia is not known and viral infection induced vasculitis cannot be ruled out.…”
Section: Discussionmentioning
confidence: 90%
“…There is no specific treatment; oral glycerol and steroids have been used and complete recovery has been reported even without any treatment. 3 We managed the case with short course of steroids without any side effects and the child started improving from day four and the recovery was complete by day eleven. Several reports suggest initiation of recovery by tenth day and reversal of pharyngeal weakness by 4-7 weeks without the use of steroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In opposition to these forms of VPI, sudden-onset VPI is less frequently reported, almost exclusively in children [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%